Effect of charge fluctuation on nanoparticle heating in dusty plasma. (27th March 2019) - Prasanna, S; Michau, A; Hassouni, K; Longo, S
Abstract: A physically consistent discrete statistical theory for charge and temperature fluctuations is developed which is capable of determining the mean and statistical properties of particle charge and temperature distributions. The statistical parameters obtained using this model are in very good agreement with Monte-Carlo simulations. Results show that the correlation between charge and temperature fluctuations significantly affect the thermal balance for nm-sized particles. We also showed that temperature distribution of nm-sized particles have a significantly populated tail towards high temperatures which may have important consequences on the structure of the particle.